Cardiorenal Effects of Kappa Opioid Peptides During Ontogeny - Wei Qi; Francine G. Smith (MDPI AG, 2011)
This review focuses on the physiological roles for kappa opioid receptors (KORs) in adult animals and humans, as well as in the developing newborn animal. Our recent findings have provided new information that under physiological conditions in conscious newborn animals, activation of KORs with the selective agonist, U-50488H, results in an aquaresis, as previously observed in adult animals and humans. In addition, we have shown in conscious lambs that KORs modulate systemic and renal haemodynamics as well as the arterial baroreflex control of heart rate, providing a previously unidentified role for KORs.